Analisis Kandungan Logam Berat Kromium (Cr) dalam Sedimen di Perairan Teluk Ambon Bagian Dalam - Matius Stefanus Batu; Marselina Theresia Djue Tea; Antho Netty Siahaya; Yeslia Utubira (Fakultas Pertanian, Universitas Timor, 2019)
Analysis of Chromium (Cr) heavy metal content in sediment have been done at inner part of Ambon Bay by using Atomic Absorption Spectrofotometer (AAS). This analysis has been done in six sampling areas, they are : Galala (the first locations), Lateri (the second location), Negeri Lama (the third location), Waeheru (the fourth location), Poka (the fifth location), and Halong (the sixth location). The study aims to determine the content of chromium metal (Cr) in sediments at inner part of Ambon Bay. The analysis showed that the Cr metal content ranged from 33.68-191.74 mg/kg. The chromium (Cr) heavy metal content in sediments is mostly among the quality standards set by the ANZECC (Australian and New Zealand Environment and Conservation Council) in 2000, which is 80-120 mg/Kg